2021
DOI: 10.3389/fpain.2021.673940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketoprofen and Morphine on Pain-Related Depression of Nestlet Shredding in Male and Female Mice

Abstract: A primary goal in pain treatment is restoration of behaviors that are disrupted by pain. Measures of pain interference indicate the degree to which pain interferes with activities in pain patients, and these measures are used to evaluate the effects of analgesic drugs. As a result of the emphasis on the expression and treatment of functional impairment in clinical settings, preclinical pain researchers have attempted to develop procedures for evaluation of pain-related functional impairment in laboratory anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Figures 13 , 14 show the effect of daily administration of 3.2 or 10 mg/kg ketoprofen on TNBS-induced depression of nesting. Note that effects of ketoprofen alone were not tested here because previous studies have found no effect of these ketoprofen doses on nesting in mice ( 5 7 ). Analysis of the time course of nesting on each day indicated that unlike morphine neither dose of ketoprofen altered TNBS-induced nesting depression on any day ( Figure 13 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 13 , 14 show the effect of daily administration of 3.2 or 10 mg/kg ketoprofen on TNBS-induced depression of nesting. Note that effects of ketoprofen alone were not tested here because previous studies have found no effect of these ketoprofen doses on nesting in mice ( 5 7 ). Analysis of the time course of nesting on each day indicated that unlike morphine neither dose of ketoprofen altered TNBS-induced nesting depression on any day ( Figure 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, nesting in mice can also be depressed by some models of experimental pain, such as intraperitoneal injection of dilute lactic acid (IP acid) as a model of acute visceral pain. IP acid-induced nesting depression is alleviated by both mu opioid receptor (MOR) agonist analgesics and non-steroidal antiinflammatory drugs (NSAIDs) (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the development of novel, selective, low-efficacy MOR agonists may represent a promising path for analgesic drug development ( 32 34 ). MOR efficacy may be especially relevant for opioid effects in assays of pain-depressed behavior, where opioids can produce competing effects that include both analgesia (which alleviates pain-related behavioral depression and increases rates of the target behavior) and motor impairment (which can reduce rates of the target behavior and obscure analgesic restoration of pain-depressed behavior) ( 19 , 34 , 35 ). Accordingly, we manipulated MOR efficacy by testing both (a) a set of single-molecule opioids with decreasing MOR efficacy (fentanyl > buprenorphine > naltrexone) ( 34 , 36 , 37 ), and (b) a series of fixed-proportion fentanyl/naltrexone mixtures that vary in net MOR efficacy as described previously ( 36 , 38 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…36,46 Furthermore, test duration and time of day are not consistent between protocols. 35 It is, therefore, possible that a different nesting protocol after SNI could reveal a phenotype as others have already shown across different pain-related models. 3,9,47,53 The same is true for our sucrose preference results (Fig.…”
Section: Discussionmentioning
confidence: 94%